Cyclical Fluctuations in the Volume of Mining, 1913-23 - Boody, Elizabeth (The Review of Economics and Statistics, 1924)
N this article, monthly indexes are presented for the output of each of 7 important minerals, various groups of these minerals, and for all groups combined. These indexes, which are adjusted for seasonal influences and long-time trend, make it possible to reach certain conclusions with respect to the cyclical fluctuations in mining activity. Of the minerals comprising our final index, copper, zinc, and iron ore respond quickly and violently to changes in business prosperity; bituminous coal is fairly sensitive to general business conditions, while anthracite coal, petroleum, and silver are much less influenced. The metals, as a whole, exhibit a wider range of cyclical fluctuations than do the non-metals, which are dominated by the fuel group. The final index of the volume of mining fluctuates in sympathy with other volume series published by the Harvard Economic Service, such as the index of trade and the index of the volume of manufacture.' The similarity of movement is shown in Charts i and 2.